The exploration of attitudes and perspectives of mental health workers on peer support in Singapore - Siong Yin Chua; Karel Himawan (Discover Mental Health)
Abstract Background Using the lived experience as their expertise, peer support specialists (PSS) focus on the empowerment of individuals with mental health conditions. Despite its value, peer support services in Singapore are relatively uncommon. Perspectives from mental health workers may provide insights on targeted strategies to address the organisational changes needed for the continued growth of the lived experience workforce. Aims The study aims to explore the attitudes and perceptions of mental health workers regarding the benefits, challenges, and potential strategies in the implementation of peer support services across mental health settings in Singapore. Methods A total of 59 responses were gathered for an online survey via convenience sampling. Descriptive statistics were generated for quantitative data, while an inductive thematic analytic method was utilised for qualitative inputs. The coding and refinement of themes were discussed between both authors. Results The majority of the respondents were willing to accept PSS as a healthcare profession (72.9%), willing to work with PSS (89.8%) and perceived there should be PSS where they worked (64.4%). Key themes identified highlighted a supportive and inclusive workplace environment, the power of the lived experience, and recovery-oriented contribution as the underlying benefits and potential challenges in implementing PSS in Singapore. Implications Policymakers could consider funding initiatives and regulatory standards to support the implementation of PSS across mental health settings in Singapore, while organisations could implement training programmes and supervision targeted at enhancing the practice of recovery-oriented care amongst its staff.